2014
DOI: 10.1074/jbc.m113.530287
|View full text |Cite
|
Sign up to set email alerts
|

Activated Platelets Interfere with Recruitment of Mesenchymal Stem Cells to Apoptotic Cardiac Cells via High Mobility Group Box 1/Toll-like Receptor 4-mediated Down-regulation of Hepatocyte Growth Factor Receptor MET

Abstract: Background: Mesenchymal stem cells (MSC) contribute to cardiac repair after myocardial injury. Underlying molecular mechanisms remain unexplored. Results: Activated platelets inhibit recruitment of MSC to apoptotic cardiac myocytes and fibroblasts via HMGB1/TLR-4-mediated down-regulation of HGF receptor MET. Conclusion:We identify a novel mechanism by which platelets impair MSC migration to damaged cardiac cells. Significance: The cross-talk between platelets and MSC might be critical for myocardial repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 60 publications
(37 reference statements)
2
48
1
Order By: Relevance
“…We detected significant amounts of HMGB1 in CM derived from CRP/ADP-activated platelets with ELISA (p<0.02 for either combination) (Fig. 1B), indicating HMGB1 release by activated platelets, which is in accordance with recently published data [67]. The HMGB1 receptors RAGE, TLR2, and TLR4 were expressed on all monocyte preparations, as evaluated by flow cytometry (data not shown).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…We detected significant amounts of HMGB1 in CM derived from CRP/ADP-activated platelets with ELISA (p<0.02 for either combination) (Fig. 1B), indicating HMGB1 release by activated platelets, which is in accordance with recently published data [67]. The HMGB1 receptors RAGE, TLR2, and TLR4 were expressed on all monocyte preparations, as evaluated by flow cytometry (data not shown).…”
Section: Resultssupporting
confidence: 90%
“…In another study, we have shown that platelet-derived HMGB1 inhibits recruitment of regenerative mesenchymal stem cells to apoptotic tissue cells [7]. Thus, the release of HMGB1 from activated platelets favors thrombosis and inflammation and suppresses mechanisms that potentially promote tissue repair and regeneration, which we have recently validated for necrotic cell-derived HMGB1 [14].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Consistent with earlier reports, HMGB-1 was rarely detected in the plasma and was mainly an intracellular protein [103]. However, thrombin, collagen, C-reactive protein, or adenosine diphosphate induced translocation of HMGB-1 from the cytoplasm to the supernatant in platelets [104][105][106]. Interestingly, thrombin or collagen did not change the exosome secretion of purified platelets.…”
Section: Hmgb-1 and Plateletssupporting
confidence: 78%
“…Administration of a CRCR4 blocking antibody attenuated this enhancement suggesting that the CXCR4-CXCL12 axis may play an important role in MSC homing to the infarcted myocardium [101]. A possible explanation of the impaired migration comes from an in vitro study from Vogel et al in which they found that activated platelets inhibit recruitment of MSC to apoptotic cardiac myocytes and fibroblasts [102].…”
Section: Msc Migration Towards the Heartmentioning
confidence: 96%